Selective Power Conditioning in Two-Phase Three-Wire Systems Based on the Conservative Power Theory - Alonso, Augusto; Paredes, Helmo K. M. [UNESP]; Jose, A. O. Filho [UNESP]; Bonaldo, Jakson P.; Brandao, Danilo; Marafao, Fernando P. [UNESP]; IEEE (Ieee, 2019)
AC power conditioners in electric power systems have been extensively explored in the literature based on approaches mainly focused on single- and three-phase wiring topologies, remaining a significant gap in regard to applications suitable for two-phase three-wire circuitry. Therefore, this work demonstrates that the Conservative Power Theory can be employed to generate the proper reference signals for an active power filter in two-phase three-wire networks. This methodology allows to selectively synthesize reference signals in a flexible manner, providing reactive power compensation, mitigation of unbalance and harmonic currents, as well as contributing to the reduction of neutral current at point of common coupling. The proposed strategy, its implementation, and the control design of a three-leg active power filter are discussed in this paper through simulation results, demonstrating the particularities and advantages of this approach.
Keywords: Active Power Filter; Conservative Power Theory; Harmonics; Power Quality; Two-phase Three-wire; Unbalance